Therapeutic effects of repetitive transcranial magnetic stimulation on cognitive impairment in stroke patients: a systematic review and meta-analysis - Gong, Cheng; Hu, Hao; Peng, Xu-Miao; Li, Hai; Xiao, Li; Liu, Zhen; Zhong, Yan-Biao; Wang, Mao-Yuan; Luo, Yun (Frontiers in Human Neuroscience, 2023)
Background In recent years, repetitive transcranial magnetic stimulation (rTMS) has emerged as a noninvasive and painless treatment for post-stroke cognitive impairment (PSCI). However, few studies have analyzed the intervention parameters of cognitive function and the effectiveness and safety of rTMS for treating patients with PSCI. Thus, this meta-analysis aimed to analyze the interventional parameters of rTMS and evaluate the safety and effectiveness of rTMS for treating patients with PSCI. Methods According to the PRISMA guidelines, we searched the Web of Science, PubMed, EBSCO, Cochrane Library, PEDro, and Embase to retrieve randomized controlled trials (RCTs) of rTMS for the treatment of patients with PSCI. Studies were screened according to the inclusion and exclusion criteria, and two reviewers independently performed literature screening, data extraction, and quality assessment. RevMan 5.40 software was used for data analysis. Results 12 RCTs involving 497 patients with PSCI met the inclusion criteria. In our analysis, rTMS had a positive therapeutic effect on cognitive rehabilitation in patients with PSCI (P < 0.05). Both high-frequency rTMS and low-frequency rTMS were effective in improving the cognitive function of patients with PSCI by stimulating the dorsolateral prefrontal cortex (DLPFC), but their efficacy was not statistically different (P > 0.05). Conclusions rTMS treatment on the DLPFC can improve cognitive function in patients with PSCI. There is no significant difference in the treatment effect of high-frequency rTMS and low-frequency rTMS in patients with PSCI between high-frequency and low-frequency rTMS. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=323720, identifier CRD 42022323720.